CMOS Front-End of LNA for GPS and GSM wireless applications - Mudavath, Mahesh; Hari Kishore, K. (International Journal of Engineering and Technology, 2017)
This paper describes a layout of a CMOS Low Noise Amplifier for reconfigurable packages which include GPS, GSM Wi-Fi applications. The improvement of a notably linear Radio front-stop, able to function with Galileo and GPS satellite signals suitable for coexisting in a mobile opposed environment for area based offerings, pleasing the fundamental necessities for a mass market product which includes low cost, low footprint, good accuracy, low strength intake and high sensitivity. primarily based on a wideband enter matching, the LNA stages cowl all band of hobby even as reaching a great change-off between excessive gain, low noise parent and coffee electricity intake. The complete simulation analysis of the circuit results in the frequency range of 1.4 GHz to 2 GHz. The noise figure is 1.8 dB at 1.4GHz and rises to 3.4 dB at 2 GHz. The input return and output return losses (S11, S22) of the LNA at a frequency range between 1.4 GHz and 2 GHz are S11= -12 dB, S22 =-44.73 dB at 1.77 GHz and S22 =-26.47 dB at 2 GHz. The overall gain of the LNA (S21) is 13 dB at 1.4025 GHz, 3rd order input intercept point (IIP3) = -3.16 dBm and -1dB compression point is -12.56 dBm. Input Impedance of 50Î©, 3dB Power Bandwidth of 450MHz, and Power Dissipation of 2.7mW at 1.2V power supply.